Analisis Oil Losses pada Serat Fiber di Stasiun Press PT. MNO dengan Metode Fishbone Diagram - Yardani, Jesi; Fadilah, Muhammad Noor; Ulimaz, Almira; Yulianti, Wan (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2024)
Based on the results of initial observations at PKMS PT. MNO, it was found that there was oil loss in the fibers during the CPO processing process, especially at the press station. Therefore, research was carried out which aimed to analyze the factors that influence the high level of oil loss in fiber fibers at the press station of PT. MNOs. This research was carried out at PT. MNO located in Tanah Laut Regency, South Kalimantan. The research implementation period starts from 17 October 2022 to 25 January 2023. The data collection method in this research was carried out in 2 ways, namely interviews (direct observation) and literature study. The data was analyzed descriptively qualitatively by comparing the data found in the field with previous literature. The results of the analysis of oil loss at the press station in December 2022 showed that the average in week 1 (press 1) was 4.18, (press 3) 4.67, (press 4) 4.02. Week 2 (press 1) 4.41, (press 3) 4.36, (press 4) 3.97. Week 3 (press 1) 4.41, (press 3) 4.74, (press 4) 4.01 week 4 (press 1) 4.32, (press 3) 4.72, (press 4) 4 .17 which press number 3 in week 1, week 3 and week 4 does not meet company standards, namely 3.89%. From the results of the analysis that has been carried out, the appropriate treatment to prevent more severe oil loss is through routine maintenance of the press machine and the components that support the press station, repairs to the press machine by replacing worn tools, and The directive provides operators to always comply with applicable SOPs.